Synthesis of various size gold nanoparticles by chemical reduction method with different solvent polarity - Hussain, Mohamed Hasaan; Noor Fitrah, Abu Bakar; Ana Najwa, Mustapa; Low, Kim-Fatt; Nur Hidayati, Othman; Fatmawati, Adam (Springer Open, 2020)
Complicated and strict protocols are followed to tune the size of gold nanoparticles (GNPs) in chemical synthesis methods. In this study, we address the polarity of solvents as a tool for tailoring the size of GNPs in the chemical reduction method. The effects of varying polarity index of the reaction medium on synthesizing gold nanoparticles by chemical reduction method have been investigated. Ethanol as a polar solvent, ethanol–water mixture as reaction medium, L-ascorbic acid as reducing agent, and polyvinylpyrrolidone as stabilizer were used to synthesize GNPs. The polarity index of the reaction medium was adjusted by changing the volume ratio of ethanol to water. UV–Vis, dynamic light scattering (DLS), and transmission electron microscopy (TEM) characterizations reveal that the growth of nanoparticles was gradually increased (~ 22 to 219 nm hydrodynamic diameter) with decreasing value of polarity index of the reaction medium (~ 8.2 to 5.2). Furthermore, the high polarity index of the reaction medium produced smaller and spherical nanoparticles, whereas lower polarity index of reaction medium results in bigger size of GNPs with different shapes. These results imply that the mechanistic of the growth, assembly, and aggregation phenomena of ligand or stabilizer-capped GNPs strongly rely on the polarity of solvent molecules. Using the proposed methodology, wide size range of GNPs with different morphology sizes can be synthesized by simply modulating the volume percentage of organic solvent in the reaction medium.